Quality of Midwifery Care Provided to Women Admitted - Araban, marziyeh; Karimy, mahmuod; Tavousi, mahmuod; Shamsi, mohsen; Niakan Kalhori, sharareh; Khazaiyan, somayeh; Simbar, masuomeh (Advances in Nursing & Midwifery, 2014)
Abstract Back ground and aim: The World Health Organization emphasizes the evaluation of health services to improve quality of care. Because the main purpose of quality measurement is to identify the weaknesses of a program, this study aims to assess the quality of midwifery care provided to women admitted for delivery in selected hospitals of Yazd medical science university. Materials and methods: A total number of 100 women randomly selected and were included in a cross-sectional study conducted in Yazd, Iran. Data were collected in the labor and delivery wards of Shaheed Sadoughi and Afshar hospitals, between September 2010 and February 2011. A valid and reliable observation check list was used for data collection. The validity of check list was accessed by content validity and the reliability was approved by computing spearman coefficient (0. 93). The check list included 247 items covered the 26 dimension of care across labor process. Observation was done by a midwife who was not practicing at the study sites, and was especially trained in study method. Data were analyzed using SPSS 16. Results: The mean age of subjects was 24 / 43 ± 5/4 years. The Number of pregnancies of was 1 to 2 , in 64 percent of participants in the study. The results showed that the overall quality of midwifery care provided in different stages of labor, was not desirable. The highest scores of quality was related to midwife- mother communication and perennial repair, and the poorest score was related to vital sign control. Conclusion: it is essential that the authorities plan to control the services provided by staff, Installation and implementation of treatment protocols of ministry of health, informing personnel duties and holding workshops to take steps to eliminate the existing shortcomings. The protocols should be translated into action with an enhanced collaboration among midwives, obstetrics and reproductive health programmers. Key Words: quality of care, labor, midwifery care